Recent Developments of Reflectarray Antennas for Reconfigurable Beams Using Surface-Mounted RF-MEMS - Eduardo Carrasco; Mariano Barba; Manuel Arrebola; Jose A. Encinar (International Journal of Antennas and Propagation)
Some of the most recent developments in reconfigurable reflectarrays using surface-mounted RF-MEMS, which have been developed at the Universidad Politécnica de Madrid, are summarized in this paper. The results include reconfigurable elements based on patches aperture-coupled to delay lines in two configurations: single elements and gathered elements which form subarrays with common phase control. The former include traditional aperture-coupled elements and a novel wideband reflectarray element which has been designed using two stacked patches. The latter are proposed as a low cost solution for reducing the number of electronic control devices as well as the manufacturing complexity of large reflectarrays. The main advantages and drawbacks of the grouping are evaluated in both pencil and shaped-beam antennas. In all the cases, the effects of the MEMS switches and their assembly circuitry are evaluated when they are used in a 2-bit phase shifter which can be extended to more bits, demonstrating that the proposed elements can be used efficiently in reconfigurable-beam reflectarrays.